Analytical method to the determination of tetracycline in synovial fluid of cows with lameness in foot (Revista Brasileira de Ciências Farmacêuticas, 2007)
Lameness in cattle is, as a rule, accompanied by infection in the wounded area. Many antimicrobial agents of wide spectrum are used in this therapy, being the concentration of the active principle of paramount importance in the treatment. One of the most used antibiotics is the tetracycline family, having as main representants oxitetracycline and tetracycline due to their treatment success. Therefore, the present work aims the development of an analytical method which allows the determination of tetracycline by High Pressure Liquid Chromatography in sinovial fluid of dairy cows, with lameness in foot, post-administration of antibiotic by intravenous via. The analytical method presented detection and quantification limits in sinovial fluid of 38 and 50 ng/mL, respectively. Recovery of low, medium and high concentrations were higher than 75%. The method presented linearity in the dynamic range evaluated (50-15.000 ng/mL). Precision and accuracy to the low, average and high concentrations were considered suitable to perform the analyses. Tmax and Cmax of tetracycline in sinovial liquid of dairy cows with lameness in foot, after intravenous administration were 1.37h and 3471.57ng/mL, respectively.